The Effectiveness of Critical Thinking on the Iraqi EFL Learner’s Performance in Poetry - Abid Salih, Omar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at finding out the effectiveness of critical thinking (CT) as a technique on the learners' performance in poetry. It is limited to the 4th preparatory students in Iraq during the second semester of the academic year 2018-2019, those who study poetry in their syllabus. To achieve this aim, it is hypothesized that there is no significant difference between the learners' mean scores of the experimental group, who would be provided with CT, and that of the control group, who has not been exposed to the mentioned treatment. The researcher has used the experimental design and chosen randomly a sample consisting of 62 students distributed in two groups. A post-test has been constructed to measure students' performance in poetry, exposing the items of the test to a jury of experts to ensure its validity. The data has been collected and analyzed by using a t-test for two independent samples. The findings have revealed that there is a statistically significant difference between the experimental group and the control group, and it was in favor of the experimental one. In light of the findings, the researcher has drawn a number of conclusions.